Presence of multidrug resistance (MDR) and extended-spectrum beta-lactamase (ESBL) of Escherichia coli isolated from cloacal swab of broilers in several wet markets in Surabaya, Indonesia - Mustofa Helmi Effendi; WIWIEK TYASNINGSIH; YEMIMA ANGGUN YURIANTI; JOLA RAHMAHANI; NENNY HARIJANI; HANI PLUMERIASTUTI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Effendi MH, Tyasningsih W, Yurianti YA, Rahmahani J, Harijani N, Plumeriastuti H. 2021. Presence of multidrug resistance (MDR) and extended-spectrum beta-lactamase (ESBL) of Escherichia coli isolated from cloacal swab of broilers in several wet markets in Surabaya, Indonesia. Biodiversitas 22: 304-310.  The purpose of this research was to identify multidrug resistance (MDR) and extended-spectrum beta-lactamase (ESBL) of Escherichia coli from cloacal swab of broiler chicken in several wet markets in Surabaya. This study used 60 broiler chicken samples, with cloacal swab method. The samples were isolated and identified to find Escherichia coli with several procedures, MacConckey Agar (MCA), Eosin Methylene Blue Agar (EMBA), Gram staining, indole test, Methyl Red-Voges Proskauer (MR-VP), citrate, and Triple Sugar Iron Agar (TSIA). Antibiotic sensitivity test was tested by using Kirby-Bauer (Disc Diffusion Method) with antibiotics: Aztreonam, Gentamicin, Chloramphenicol, Tetracycline, and Ciprofloxacin. From research, it can be illustrated that the isolates resistant to antibiotic Ciprofloxacin were 67% and Tetracycline was 65%. Total 97% isolates were found sensitive for Aztreonam, 73% for Chloramphenicol, and 55% for Gentamicin. Twelve isolates identified for MDR and two were ESBL. It can be explained that broiler chicken from wet market should be considered as a source of transmission for MDR and ESBL of E. coli to the public health.